Matrix-vector algorithms of local posteriori inference in algebraic Bayesian networks on ideal of disjuncts - Zolotin, Andrey A.; Malchevskaia, Ekaterina A. (2016 XIX IEEE International Conference on Soft Computing and Measurements (SCM), 2016)
An alternative mathematical model of knowledge pattern is described in the article. The calculation of transition matrix from the probability estimates of ideal of disjuncts to probability estimates of ideal of conjuncts and quanta propositions are proposed. The matrix-vector notation of posteriori inference equations for knowledge patterns over ideal of disjuncts is given. Obtained results are applied to the posteriori inference equations for knowledge patterns with uncertain probability estimates.